The Microfoundations of Organizational Social Networks: A Review and an Agenda for Future Research. (July 2015) - Tasselli, Stefano; Kilduff, Martin; Menges, Jochen I.
This paper focuses on an emergent debate about the microfoundations of organizational social networks. We consider three theoretical positions: an individual agency perspective suggesting that people, through their individual characteristics and cognitions, shape networks; a network patterning perspective suggesting that networks, through their structural configuration, form people; and a coevolution perspective suggesting that people, in their idiosyncrasies, and networks, in their differentiated structures, coevolve. We conclude that individual attitudes, behaviors, and outcomes cannot be fully understood without considering the structuring of organizational contexts in which people are embedded, and that social network structuring and change in organizations cannot be fully understood without considering the psychology of purposive individuals. To guide future research, we identify key questions from each of the three theoretical perspectives and, particularly, encourage more research on how individual actions and network structure coevolve in a dynamic process of reciprocal influence.